Tamanho único: o corpo da mulher gorda na arte contemporânea - Codinotti, Fernanda Pizzutti (2020)
This master's research reflects on the fat body in contemporary society from photographs and videos, artistic-visual material prepared by the author herself. The research theme refers to my experience as a fat woman with a strong corpulence who finds herself confronted by the judgmental gaze of others and who knows that her body is seen out the current norms and standards of beauty and health idealized in contemporary times. Faced with the impossibility of hiding this imposing body, the confrontation led me to look and see it through the extreme visibility of the images. In a first moment of the research, the visibility of the fat body is given by the production of selfies. In the second moment, I made a sequence of videos and photographs of body fragments obtained in everyday situations. This work progresses in action with the mobile device. Virtually, the capturing of smartphone transforms my body. This new body, supported by conceptual issues related to the body of the fat woman, outside of normative standards, becomes a support for issues that go beyond my body as such. The imagery production extends to the femininity of the fat woman's body represented in the media and in contemporary art. Photography and video as objects of art support this poetics, in dialogue with other artists’ works and with texts by authors who contribute to the discussion of this social and human theme in the field of art - in which the shapeless becomes the shape; the unsightly becomes the aesthetic, in which beauty is undoubtedly of a different order.